Recent coral reefs and geology history of providencia island (western caribbean sea, colombia) (1986)
Providencia Island, composed of pre-Miocene and Miocene volcanic rocks, is surrounded by an extensive coral reef complex which, from east to west, can besubdivided morphologically and ecologically into the following subparallel units:a) Fore-reef terrace: a bare rocky flat, from one to several kilometers broad, sloping gently from the reef to a morphological break below 30 m which marks the beginning of the outer slope.b) Barrier reef: more than 100 m broad and totalling some 30 km in length, it rises up to near low-tide level. Coherent in the north and in the south, its middle section is a chain of coral pillars. A profuse growth of MiIIepora,Palythoa and abundant coralline algae covers the reef crest, where locally a true algal ridge is developed.c) Lagoon: includes a broad and shallow lagoonal terrace adjacent to barrier reef and a deeper lagoon basin, both locally connected by steep "sand cliffs".  From the lagoon floor, covered by bare sand and coral rubble, numerouspatch reefs and coral heads to various heights.d) Leeward shelf: rocky flats with scattered coral growth extend from the shore to a steep escarpment at 20 or more meters depth marking the beginning of the western outer slope. Patch reefs and sandy flats are equally abundant.Submarine terraces, escarpments and valleys, as well as an irregular outline of many reefs reflect a complex geomorphological history of the insular shelf duringPleistocene, which is in part concealed by Holocene reef growth and sedimentation.